Fibronectin Promotes the Malignancy of Glioma Stem-Like Cells Via Modulation of Cell Adhesion, Differentiation, Proliferation and Chemoresistance - Yu, Qi; Xue, Yixue; Liu, Jing; Xi, Zhuo; Li, Zhen; Liu, Yunhui (Frontiers in Molecular Neuroscience, 2018)
Glioma stem-like cells (GSCs) are regarded as the sources of oncogenesis, recurrence, invasion and chemoresistance in malignant gliomas. Growing evidence suggests that the microenvironment surrounding GSCs interacts with tumor cells to influence biological behavior; however, the functional mechanisms involved are still unclear. In the present study, we investigated the modulation of GSCs triggered by fibronectin (FN), a main component of the extracellular matrix (ECM), in terms of cell adhesion, differentiation, proliferation and chemoresistance. We demonstrated that pre-coated FN prompted increased adherence by GSCs, with increased matrix metallopeptidases (MMPs)-2 and -9 expression, in a concentration-dependent manner. Decreases in sox-2 and nestin levels, and increased levels of glial fibrillary acidic protein (GFAP) and β-tubulin were also found in GSCs, indicating cell differentiation driven by FN. Further investigation revealed that FN promoted cell growth, as demonstrated by the elevation of Ki-67, with the activation of p-ERK1/2 and cyclin D1 also evident. In addition, FN suppressed p53-mediated apoptosis and upregulated P-glycoprotein expression, making GSCs more chemoresistant to alkylating agents such as carmustine. In contrast, this effect was reversed by an integrin inhibitor, cilengitide. Activation of the focal adhesion kinase/paxillin/AKT signaling pathway was involved in the modulation of GSCs by FN. Focusing on the interactions between tumor cells and the ECM may be an encouraging aspect of research on novel chemotherapeutic therapies in future.